Strain-specific probiotic (microbial cell preparation) and omega-3 fatty acid in modulating quality of life and inflammatory markers in colorectal cancer patients: a randomized controlled trial - Golkhalkhali, Babak; Rajandram, Retnagowri; Paliany, Audra Shaleena; Ho, Gwo Fuang; Ishak, Wan Zamaniah Wan; Johari, Che Shafini; Chin, Kin Fah (Wiley, 2017)
Aim: Colorectal cancer patients on chemotherapy usually have elevated levels of inflammatory markers and experience numerous side effects from chemotherapy thereby leading to poor quality of life. Omega-3 fatty acid and microbial cell preparation (MCP) have been known to provide significant benefits in patients on chemotherapy. The aim of this study was to determine the effect of supplementation of omega-3 fatty acid and MCP in quality of life, chemotherapy side effects and inflammatory markers in colorectal cancer patients on chemotherapy. Methods: A double-blind randomized study was carried out with 140 colorectal cancer patients on chemotherapy. Subjects were separated into two groups to receive either placebo or MCP [30 billion colony-forming unit (CFUs) per sachet] at a dose of two sachets daily for 4 weeks, and omega-3 fatty acid at a dose of 2 g daily for 8 weeks. Outcomes measured were quality of life, side effects of chemotherapy and levels of inflammatory markers such as interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) and C-reactive protein. Results: The supplementation with MCP and omega-3 fatty acid improved the overall quality of life and alleviated certain side effects of chemotherapy. The supplementation with MCP and omega-3 fatty acid also managed to reduce the level of IL-6 (P = 0.002). There was a significant rise in the placebo group's serum TNF-α (P = 0.048) and IL-6 (P = 0.004). Conclusion: The combined supplementation with MCP and omega-3 fatty acid may improve quality of life, reduce certain inflammatory biomarkers and relieve certain side effects of chemotherapy in colorectal patients on chemotherapy.